KAUSALITAS PERTUMBUHAN EKONOMI,KEMISKINAN,PENDIDIKAN DAN DISTRIBUSI PENDAPATAN DI PULAU SUMATERA - Adriani, Syafika; Sentosa, Sri Ulfa (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstrack :This study aims to determine the causality relationship between Economic Growth, Poverty, Education and Distribution of Income on the island of Sumatra by using a panel model Vector Autoregresion panel (PVAR) from 2013 to 2017. The research methods used are: (1) Analysis of the Vector Regression Panel , (2) Granger Causality Test. The results showed that (1) there was no causality or one-sided relationship between economic growth and poverty on the island of Sumatera, (2) there was no causality relationship between poverty and income distribution in Sumatera Island, but there was a one-way relationship between poverty and income distribution. (3) There is no causal relationship or one-way relationship between income distribution and education on the island of Sumatera (4) There is no causal relationship between education and economic growth, but there is a one-way relationship between education and economic growth on the island of Sumatera. (5) There is no causality or one direction relationship between growth and income distribution on the island of Sumatera. (6) There is no causal relationship between education and poverty, but there is a one-way relationship of poverty to education on the island of SumateraKeywords: Economic Growth, Poverty, education, Income Distribution